IMPLEMENTATION OF QUIZIZZES IN IMPROVING ELEMENTARY STUDENTS' COMPUTATIONAL THINKING IN MATHEMATICS LEARNING - Gita Raviesta Putri Gita Raviesta Putri; Jonni sitorus; Siti Mayang Sari (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This research aims to explore the implementation of Quizizz media in improving primary school students' computational thinking skills in learning mathematics. A qualitative approach was used with a case study method, involving classroom observation, in-depth interviews with teachers, and analysis of student learning outcomes. The research subjects were elementary school students SD XYZ in Medan City. who were involved in using Quizizz as a learning tool. The results showed that the integration of Quizizz effectively increased students' learning motivation, strengthened understanding of mathematical concepts, and developed computational thinking skills, such as decomposition, abstraction, pattern recognition, and algorithms. Teachers also reported that Quizizz facilitated interactive and problem-solving orientated learning. This research emphasises the importance of using innovative educational technology in improving the quality of mathematics learning at the primary school level.